RF Rectifier with High Efficiency over a Wide Input Power Range Using a Voltage Controlled Switch in a ‘Handover’ Fashion - Abdulkadir Muhammad, Lawan; Hieng Tiong, Su; Yi Lung, Then; Jia Fen, Zhou (2020)
Wireless energy transfer gains from the option of receiving power from multiple sources with different power levels. This paper presents a rectifier that maintains good efficiency over a wide input power range at 2.45 GHz frequency using a MOSFET as the voltage controlled switch (VCS). The VCS performs a `handover' function between a low threshold voltage diode and a high breakdown voltage diode in a seamless manner without interrupting power supply to the load. This topology has only so far produced good results at lower frequencies. An L-matching network is used to achieve impedance matching over the input power range at 2.45 GHz with the help of a blocking capacitor acting as a high pass filter. Simulated results show that the rectifier can maintain its RF to DC conversion efficiency above 50% from 3 to 23.8 dBm. A peak efficiency of 73% at 16.6 dBm is also recorded.